Acute macular neuroretinopathy as the first stage of SARS-CoV-2 infection. Issue 3 (May 2023) - Capuano, Vittorio; Forte, Paolo; Sacconi, Riccardo; Miere, Alexandra; Mehanna, Carl-Joe; Barone, Caterina; Bandello, Francesco; Souied, Eric H.; Querques, Giuseppe
Introduction: To report two cases of Acute Macular Neuroretinopathy (AMN) presented as the first stage of SARS-CoV-2 infection in two European countries during the third wave of pandemic viral infection in the early months of 2021. Observations: A unilateral case of type 1 AMN in a man and a bilateral case of type 2 AMN in an otherwise heathy patients were reported. Sudden onset of paracentral scotoma characterized the cases with no systemic symptoms. Structural optical coherence tomography (OCT) shows multifocal middle and inner retinal hyperreflective infarctions. OCT-Angiography showed the presence of hypoperfusion of the deep capillary plexus (DCP) corresponding to the hyperreflective lesions visible on structural OCT, confirming the diagnosis. Conclusions and importance: Type 1 and type 2 AMN may be the first stage of SARS-CoV-2 infection. We suggest testing all patients with AMN for SARS-CoV-2. In our cases, the natural history of AMN associated with SARS-CoV-2 infection was similar to already described cases of AMN.